Red Cell Distribution Width Value Supports the Diagnosis of Neonatal Sepsis in 34-42 Week Gestational Age Neonates - Stevanny, Bella; Akbari, Atika; Mariana (Journal of Nepal Paediatric Society, 2021)
Introduction: Neonatal sepsis is an emergency because delayed treatment can be fatal, whereas the diagnosis is challenging because of the unspecific clinical manifestation. Bacterial culture is the gold standard for the diagnosis, but it takes several days to get the results, which often come out as negative. This study aims to determine the diagnostic value of RDW to support the diagnosis of neonatal sepsis in 34 – 42 week gestational age neonates. Methods: This cross-sectional diagnostic study used secondary data obtained from Medical Record Installation and Clinical Pathology Laboratory of Dr. Mohammad Hoesin General Central Hospital in Palembang, Indonesia. One hundred and thirty-four medical records were statistically analysed using Med Calc Version 19 to determine the cut-off point and diagnostic value of RDW in the diagnosis of neonatal sepsis. Results: One hundred and thirty-four subjects consisting 32 septic neonates (23.9%) and 102 non-septic neonates (76.1%) were reviewed. Most of them were males (80/134) and preterm (73/134) with normal birth weight (99/134). At the cut-off point of > 16.2%, RDW value was significantly able to predict neonatal sepsis (p = 0.000, p < α) with prediction power (AUC) of 0.780 (fair). The diagnostic values were sensitivity 84.37%, specificity 57.84%, positive predictive value 38.57%, negative predictive value 92.19%, positive likelihood ratio 2.00 and negative likelihood ratio 0.27. Conclusions: Red cell distribution width value might potentially be used as a diagnostic marker to support the diagnosis of neonatal sepsis in 34 – 42 week gestational age neonates. However, further study is needed to support this statement.